Sector Analysis of Islamic Capital Markets and Artificial Intelligence Functioning as Sharia Advisors - Widhy Setyowati; Intan Sri Rahayu (International Transactions on Artificial Intelligence, 2023)
Artificial intelligence technologies will have a significant impact on a variety of career areas, including jobs in finance and law. The fact is that the Islamic capital market sector tends to use AI technology. There are now proposals to replace the role of sharia advisors with AI technology. The research conducted is legal research using qualitative methods. The legal historiographical approach was chosen to show the responsibility of the sharia board in realizing the concept of Islamic urbanism. The idea of Islamic urbanism is closely related to AI technology and the capital market as the main places for both of them to work in cities. This research has three objectives. It analyzes the role and function of artificial intelligence technology, Islamic capital markets, and the part of Sharia Advisors in the industry. Then the problem of using AI technology in the Islamic capital market is identified. Moreover, it offers a solution to using the proposed innovative technology. This paper argues that the ability of technology to replace the role of Islamic advisors in the Islamic capital market sector is limited. This is because AI technology, although advanced, can only deal with the physical world of cities but still needs to embody the concept of Islamic urbanism. At the same time cannot replace the role of sharia advisors.